Fundamentals of communications and networking - Solomon, Michael 1963- 4 0 (Michael G.),16; (Information technology security consultant), Kim, David;Carrell, Jeffrey L.; 5 (Burlington, MA : Jones & Bartlett Learning, 2015)
Networks ahve long been regarded as methods to connect resources. While this is still the case, today's networks are required to support an increasing array of real-time communication methods. Video chat, real-time messaging, and always-connected resources put demands on networks that were previously unimagined. The Second Edition of Fundamentals of Communications and Networking helps readers better understand today's networks and the way they support the evolving requirements of different types of organisations. It discusses the critical issues of designing a network that will meet an organisation's performance needs and discusses how businesses use networks to solve business problems. This book prepares readers to proficiently understand and design modern networks.--Page [4] of cover.
Includes bibliographical references (pages 473-474) and index.
Keywords: 2 -- 0; 6; Management.;Distributed processing.;Computer networks. -- Computer networks.;Telecommunication systems;Electronic data processing;Business communication -- 20; 20; 2